Fog at Santacruz Airport (MAUSAM, 1952)
A study of fogs that occurred at Santaeruz Airport during the period 1944 to 1951 has been made. It is found that while fog did not occur at all during certain years, as many as 7 fogs occurred in 1945 and 5 In 1951. Fog occurs mostly during the months of February and March. Synoptic situations associated  with days of fog have been discussed and a method of forecasting fog has been indicated. A fog prediction diagram for Santacruz has been described and its usefulness tested with reference to actual data for the winter season' of 1948 and 1950. A comparison has been made of fogs at Drigh Road Airport, Karachi and those at Santacruz.